2020
DOI: 10.1021/acsabm.0c01201
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation-Induced Electrochemiluminescence Immunosensor Based on 9,10-Diphenylanthracene Cubic Nanoparticles for Ultrasensitive Detection of Aflatoxin B1

Abstract: 9,10-Diphenylanthracene cubic nanoparticles (DPA CNPs) with aggregation-induced emission characteristic (AIEgens) were synthesized through a facile reprecipitation method; then, a bright and stable electrochemiluminescence (ECL) signal can be observed when the DPA CNPs were modified at the glassy carbon electrode (GCE) in the presence of Tri-n-propylamine (TPA). This phenomenon is ascribed to the molecules with restricted movement that greatly blocked the energy leakage during the relaxation of the excited sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Fang et al prepared AIE-active cubic NPs from the reprecipitation of 9,10-diphenylanthracene, which was used to fabricate ECL-based AFB 1 sensor over glassy carbon electrode (GCE), after functionalizing with PEI, and then AFB 1 -antibody and BSA via glutaraldehyde cross-linker. 331 In the presence of tripropylamine (TPrA), a strong ECL signal at 460 nm could be registered but the selective binding of AFB 1 to the antibody led to the gradual decrease in ECL due to protein quenching effect on the NPs’ fluorescence. Li, Tang, and Zhang et al developed a lateral flow biosensor ( C100 ) to simultaneously detect mycotoxins AFB 1 and cyclopiazonic acid (CPA) in food samples within 8 minutes.…”
Section: Sensing For Environmental Monitoring and Food Safetymentioning
confidence: 99%
“…Fang et al prepared AIE-active cubic NPs from the reprecipitation of 9,10-diphenylanthracene, which was used to fabricate ECL-based AFB 1 sensor over glassy carbon electrode (GCE), after functionalizing with PEI, and then AFB 1 -antibody and BSA via glutaraldehyde cross-linker. 331 In the presence of tripropylamine (TPrA), a strong ECL signal at 460 nm could be registered but the selective binding of AFB 1 to the antibody led to the gradual decrease in ECL due to protein quenching effect on the NPs’ fluorescence. Li, Tang, and Zhang et al developed a lateral flow biosensor ( C100 ) to simultaneously detect mycotoxins AFB 1 and cyclopiazonic acid (CPA) in food samples within 8 minutes.…”
Section: Sensing For Environmental Monitoring and Food Safetymentioning
confidence: 99%
“…Thus, a free-label sensor was prepared based on DPA CNPs, and acceptable detection was realized. 114…”
Section: Application In Small Moleculesmentioning
confidence: 99%
“…One of the first observations of ECL involved 9,10-diphenylanthracene (DPA) as luminophore [6]; recently, DPA cubic NPs (CNPs) have been exploited for the construction of an AIECL immunosensor for the detection of the mycotoxin aflatoxin B 1 (AFB 1 ) [63]. The authors observed an important increase of the ECL signal when the DPA CNPs were deposited on the GCE surface in comparison with the signal observed when the NPs were dispersed in the solution.…”
Section: Small Molecule-based Aieclmentioning
confidence: 99%